Economic Sovereignty of a State: Value, Challenges, Legal Mechanisms for Protection - Oleg Yu. Boldyrev; Levan T. Chikhladze (Антиномии, 2022)
Sovereignty is seen as one of the hallmarks of a state, however globalization and integration processes challenge state sovereignty. First of all, they challenge the economic component of state sovereignty – the so-called economic sovereignty. Many states, while de jure sovereign, do not have full sovereignty de facto. This problem is also relevant for Russia: it remains highly dependent on imports of high-tech products, on foreign components, foreign standards, foreign software products and payment systems. Although measures to address these problems were proclaimed, their effectiveness is doubtful. It seems that the ongoing financial and economic policy and some changes in Russian legislation (in particular, tax legislation) don’t contribute to genuine import substitution. Moreover they create difficulties for it. Of course, political scientists, economists and philosophers argue whether the value of state sovereignty is preserved in the modern world. But for lawyers the answer is obvious: sovereignty is one of the key principles of both international law and the constitutional law of most states. However, lawyers sometimes “do not notice” the threats to sovereignty, believing that sovereignty is a formal concept, not an actual one. According to many lawyers, the transfer of the powers of the state to supranational unions is not a limitation of sovereignty. It seems that such an approach only camouflages the problem, and does not contribute to its solution. Moreover, foreign experience indicates the possibility of using different terminology (“transfer of powers”, “transfer of sovereign rights”, “restriction of sovereignty”, etc.) for similar phenomena. The article draws attention to some of the threats to economic sovereignty that Russia has faced, and which are associated with public debt, various international obligations. New sanctions in connection with a change in the geopolitical situation in 2022 actualize this issue: dependence on imports of critically important products, on foreign software; disconnection Russia from the SWIFT system; termination of Visa and Mastercard payment systems in Russia; freezing of Russian reserves, etc. The authors of the article conclude that although one of the arguments in favor of the constitutional reform of 2020 was the protection of state sovereignty, a number of problems in this part remain unresolved. No constitutional restrictions on external borrowing have been introduced. Complicated procedures for the conclusion of those international agreements that may lead to limitation of the economic sovereignty of the state have not been established; other mechanisms for ensuring state sovereignty, which have already been tested in foreign experience, have not been used. Therefore, the relevance of further constitutional reform in terms of ensuring economic sovereignty remains.